Microperimetry in Age-Related Macular Degeneration: An Evidence-Base for Pattern Deviation Probability Analysis in Microperimetry - Cassels, Nicola K. (Transl Vis Sci Technol, 2019)
PURPOSE: The “traffic light” color designation of differential light sensitivity used in a number of microperimeters does not encompass the conventional Total and Pattern Deviation probability analyses adopted by standard automated perimetry. We determined whether the color designation is indicative of abnormality as represented by the “gold standard” Pattern Deviation probability analysis. METHODS: Total and Pattern Deviation probability levels, using two different methods, were derived at each of 40 stimulus locations, within 7° eccentricity, from 66 ocular healthy individuals (66 eyes) who had undergone microperimetry with the Macular Integrity Assessment microperimeter. The probability levels were applied to the corresponding fields from each of 45 individuals (45 eyes) with age-related macular degeneration (AMD) and evaluated in relation to the color designation. RESULTS: Sensitivities designated in orange encompassed the entire range of Pattern Deviation probability levels (from normal to P ≤ 1%). Those designated in green were mostly normal; those in red/black generally corresponded to the ≤1% probability level. CONCLUSIONS: The green and the red/black designations are generally indicative of normal and abnormal probability values, respectively. The orange designation encompassed all probability outcomes and should not be relied upon for visual field interpretation. The evidence base indicates replacement of the color designation of sensitivity in AMD by Total Deviation and Pattern Deviation analyses. TRANSLATIONAL RELEVANCE: The use of Total and Pattern Deviation probability analyses is not universal in all microperimeters, and the derivation of these values indicates that color coding will lead to errors in evaluating visual field loss.